A Unified Strategy for Kainoid Synthesis. Issue 22 (23rd June 2014) - Fujii, Masaya; Yokoshima, Satoshi; Fukuyama, Tohru
Abstract: A unified strategy for kainoid synthesis was developed. The key features of the strategy involve a Claisen–Ireland rearrangement to construct the contiguous stereogenic centers and a palladium‐catalyzed formation of the pyrrolidine ring with complete stereoselectivity. The present protocol has enabled rapid access to a wide range of kainoids with diverse types of substituents (alkenyl, aryl, and alkyl groups) at the 4‐position of the pyrrolidine ring, starting from the common intermediate and appropriate acetic acid derivatives. To test the generality of the strategy, we have accomplished the syntheses of kainic acid, o ‐methoxyphenyl derivative (MFPA), and a novel cyclopropyl derivative (CPKA), using 3‐methylbut‐3‐enoic acid, 2‐(2‐methoxyphenyl)acetic acid, and 2‐cyclopropylacetic acid, respectively. Abstract : The syntheses of kainic acid, MFPA, and a cyclopropyl analog of kainic acid (CPKA) have been accomplished from a common intermediate. A unified strategy was used, featuring a Claisen–Ireland rearrangement to construct the contiguous stereogenic centers, and a palladium‐catalyzed formation of the pyrrolidine ring with complete stereoselectivity.